The specter of materialism : queer theory and Marxism in the age of the Beijing consensus - Liu, Petrus (Duke University Press, 2023)
"In The Specter of Materialism Petrus Liu examines what "materialism" means for progressive queer theory and Marxist approaches to China's postsocialist economy. Liu recasts the history of queer theory in light of the Beijing Consensus, arguing that North American queer theory's inability to sustain a materialist analysis is the result of its positioning of the United States, rather than China, as the focal point of contemporary global capitalism. Analyzing relations of gender and sexuality that have been reconfigured by China's global capitalist accumulation-such as dagongmei (female migrant laborers in China's export-oriented sunbelt) and money boys (rural-to-urban sex workers)-Liu argues for a materialist queer theory that positions China at the center."--